Analisis Postur Kerja Pada Proses Pemasangan Gas Cng Di PT. Surya Pamenang Menggunakan Metode RULA Dan REBA - Risky Ilham Wardana; Sri Rahayuningsih; Lolyka Dewi Indrasari (JATI UNIK : Jurnal Ilmiah Teknik dan Manajemen Industri, 2021)
PT. Surya Pamenang is a company engaged in the paper industry located in kediri – East Java. In the company requires fuel that is CNG gas. In the process of use, conventional installation is needed by understanding ergonomic movement posture. The purpose of this study to find out the most dominant complaints in CNG gas installation workers was reviewed from the results of nordic body maps questionnaire processing and the recommendation of improving safe working posture based on the results of RULA and REBA scores for workers in the CNG gas installation section. Data collection is done by means of the dissemination of Nordic Body Maps questionnaires and the provision of recommendations for improvement of safe working posture based on the results of RULA and REBA scores for workers in the CNG gas installation section. Data collection is done by distributing Nordic Body Maps questionnaires to CNG gas installation workers. The results of the study were complaints from the most dominant workers on the installation of CNG gas at the opening of the CNG gas door, valve opening and condensate cleaning, namely on the upper neck, lower neck, right shoulder, back, waist, left calf. The recommendation given is to be given lubricant and remove rust - rust, continuous energy when turning the valve and liver , accompanied by standing every 10 minutes to reduce back and waist pain, cube-shaped climbing is needed, extensive addition is needed to the CNG gas door area and relaxation and rungs amounting to 6 units to facilitate the work. PT. Surya Pamenang adalah perusahaan yang bergerak dibidang industri kertas yang berada di wilayah Kediri – Jawa Timur. Didalam perusahaan tersebut membutuhkan bahan bakar yaitu gas CNG. Didalam proses penggunaannya diperlukan pemasangan secara konvensional dengan memahami postur gerakan yang ergonomi. Tujuan penelitian ini untuk mengetahui keluhan yang paling dominan pada pekerja pemasangan gas CNG ditinjau dari hasil pengolahan kuisioner Nordic Body Maps dan pemberian rekomendasi perbaikan postur kerja yang aman berdasarkan hasil skor RULA dan REBA bagi pekerja pada bagian pemasangan gas CNG. Pengumpulan data dilakukan dengan cara penyebaran kuesioner Nordic Body Maps kepada pekerja pemasangan gas CNG. Hasil dari penelitian adalah keluhan dari pekerja paling dominan pada pemasangan gas CNG pada bagian pembukaan pintu gas CNG, pembukaan valve dan pembersihan kondensat yaitu pada bagian tubuh leher bagian atas, leher bagian bawah, bahu kanan, punggung, pinggang, betis kiri. Rekomendasi yang diberikan adalah diberikan pelumas dan dihilangkan karat – karat, tenaga yang kontinu saat memutar valve dan hati – hati, diiringi berdiri setiap 10 menit untuk mengurangi nyeri punggung dan pinggang, diperlukan panjatan berbentuk kubus, diperlukan penambahan luas pada area pintu gas CNG dan dilakukan relaksasi dan anak tangga berjumlah 6 unit untuk mempermudah pekerjaan.